1988
DOI: 10.1113/jphysiol.1988.sp016955
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ongoing and reflex discharge of single splenic and renal sympathetic postganglionic fibres in cats.

Abstract: SUMMARY1. Electrical discharge of thirty-nine single splenic and renal postganglionic nerve fibres was recorded in artificially respired, chloralose-anaesthetized cats.2. Ongoing discharge rates, averaged over 10 s periods, did not differ between renal and splenic fibres. All neurones of both groups had irregular discharge frequencies.3. Half of the splenic population and all renal fibres had cardiac-related discharge patterns. Of those tested for respiratory-related firing, 30 % of the splenic fibres and 69% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…This conclusion could not have been reached in microneurographic recordings of multiunit sympathetic bursts, which have been the standard approach to recording from postganglionic sympathetic fibres in human peripheral nerves. The maximum number observed within a burst was seven, which is also what Hallin & Torebjork (1974) (0 5-3 Hz;Jainig, 1985), as well as from renal, splenic and mesenteric nerves in the cat (0-03-6-4 Hz, median 0 9 Hz; Meckler & Weaver, 1988;Stein & Weaver, 1988). It should be noted, however, that our subjects had low levels of spontaneous multiunit activity (range 9-17 bursts min-').…”
Section: Latency Variationsmentioning
confidence: 93%
See 1 more Smart Citation
“…This conclusion could not have been reached in microneurographic recordings of multiunit sympathetic bursts, which have been the standard approach to recording from postganglionic sympathetic fibres in human peripheral nerves. The maximum number observed within a burst was seven, which is also what Hallin & Torebjork (1974) (0 5-3 Hz;Jainig, 1985), as well as from renal, splenic and mesenteric nerves in the cat (0-03-6-4 Hz, median 0 9 Hz; Meckler & Weaver, 1988;Stein & Weaver, 1988). It should be noted, however, that our subjects had low levels of spontaneous multiunit activity (range 9-17 bursts min-').…”
Section: Latency Variationsmentioning
confidence: 93%
“…In the present material short interspike intervals, with instantaneous frequencies greater than 50 Hz, were produced by nine units, but only 2-4% of all intervals were so short. Single vasoconstrictor motoneurones in the renal, splenic and mesenteric nerves of the cat also generate high instantaneous firing rates, up to 59 Hz, and the frequency distribution is similarly broad (Meckler & Weaver, 1988;Stein & Weaver, 1988). Such erratic instantaneous frequencies may be physiologically appropriate; electrical stimulation of sympathetic nerves has shown that irregular interstimulus intervals are more effective than regular stimuli for contracting arterioles in the muscle vascular bed of the cat, the optimal pattern being a 32 Hz stimulus applied at 4 s intervals (Andersson, 1983).…”
Section: Latency Variationsmentioning
confidence: 99%
“…More importantly, sympathetic neurones do not fire at such high rates. For instance, the median firing rate of single sympathetic neurones in the renal, splenic and mesenteric nerves in the anaesthetized cat is 0.9 Hz (Meckler & Weaver, 1988;Stein & Weaver, 1988), and in awake humans, individual cutaneous vasoconstrictor and sudomotor neurones discharge very irregularly with an average frequency of 0.5-0.6 Hz during the specific increases in sympathetic drive associated with cold-induced vasoconstriction (Macefield & Wallin, 1999b) or heat-induced sweating (Macefield & Wallin, 1996). Moreover, human muscle vasoconstrictor neurones There is evidence in experimental animals that, in addition to receiving fusimotor drive, muscle spindles are subject to modulation by the sympathetic nervous system.…”
mentioning
confidence: 99%
“…The origin of this sympathetic firing is unknown. Sympathetic reflexes can be elicited by activation of a variety of visceral afferent nerves in spinal animals (Meckler & Weaver, 1988;. In preliminary experiments in our laboratory, blockade of afferent nerve activity by cooling the intestine produced decreases in mesenteric nerve activity before (35%) and after (16%) spinal cord transection in rats, suggesting that tonic excitatory afferent inputs may provide some on-going activity of these nerves.…”
Section: Discussionmentioning
confidence: 99%